Comparison of the Effectiveness of Acceptance and Commitment Therapy and Meaning Therapy Based on Rumi’s Teachings on Life Enthusiasm and Health Anxiety in Men with Stomach Cancer - Ansari , Kosar; Noruzi , Asghar; Khalili, Gholamreza (Iranian Journal of Neurodevelopmental Disorders, 2024)
Objective: The purpose of this study was to compare the effectiveness of Acceptance and Commitment Therapy (ACT) and Meaning Therapy based on Rumi’s teachings on life enthusiasm and health anxiety in men with stomach cancer. Methods and Materials: The research method was quasi-experimental, utilizing a pretest-posttest design with two experimental groups and a control group, including a follow-up phase. The statistical population consisted of all men with stomach cancer hospitalized at Imam Khomeini Hospital in Sari during 2023–2024. From this population, 45 individuals were selected using convenience sampling and assigned to three groups. The research instruments included the Life Enthusiasm Questionnaire by Hassanzadeh (2015) and the Health Anxiety Questionnaire by Salkovskis and Warwick (2002). To analyze the hypotheses, preliminary tests (Shapiro-Wilk, M-Box, and Mauchly’s test of sphericity), multivariate analysis of variance (MANOVA) with repeated measures, and Bonferroni adjustment were employed. Findings: Results indicated a significant difference in life enthusiasm scores between the ACT group, the Meaning Therapy group based on Rumi’s teachings, and the control group, with improvements observed compared to the control group (p < .01). Moreover, ACT demonstrated superior effectiveness in improving life enthusiasm. Similarly, a significant difference in health anxiety scores was found between the ACT group, the Meaning Therapy group based on Rumi’s teachings, and the control group, with improvements noted compared to the control group (p < .01). ACT also showed superior performance in reducing health anxiety. Conclusion: Both interventions improved life enthusiasm and reduced health anxiety, with ACT demonstrating superior effectiveness. Results highlight the lasting impact and clinical relevance of these psychological interventions for cancer patients.